PENGARUH PEMBERIAN UMPAN BALIK DARI TEMAN SEJAWAT TERHADAP KEMAMPUAN KEMAMPUAN BERPIKIR KRITIS DAN KOMUNIKASI MATEMATIS SISWA SMP LABORATORIUM UNDIKSHA SINGARAJA - Purwadi, I Made Ari (Undiksha, 2020)
Critical thinking and communication skills are two of the skills that must be possessed by Indonesian children to be able to compete in the 21st century. Therefore, the research that was conducted at SMP Laboratorium Undiksha at 2018/2019 academic year was aimed at determining the effect of peer feedback toward students' critical thinking and mathematical communication. This quasi-experiment research used a post-test only control group design in a population that consists of 98 students and spread at 4 classes. Experiments in the form of implementing peer feedback were applied to the experimental class and teacher feedback was applied to the control class and it was done at 8 meetings. Then, the sample was taken using cluster random sampling technique. The data of this research were the score of critical thinking and mathematical communication and it was collected by essay and analyzed using Manova test at a significance level of 5%. The significance value obtained through the results of the manova test was equal to 0.034. If compared with the significance level of 5%, then the significance value was smaller 0,05. It was decided to reject H0. Thus, it was able to be concluded that students 'critical thinking and mathematical communication skills in the experimental class were significantly better than students' critical thinking and mathematical communication skills in the control class